2011
DOI: 10.1093/abbs/gmr064
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility group protein N2 (HMGN2) inhibited the internalization of <italic>Klebsiella pneumoniae</italic> into cultured bladder epithelial cells

Abstract: Since bacterial invasion into host cells is an important step in the infection process, using the agents to interfere with bacterial internalization is an attractive approach to block the infection process. In this work, we describe a new, previously unrecognized role of the human cationic host defense peptide HMGN2 during Klebsiella pneumoniae infections. Our results revealed that the internalization of K. pneumoniae strain 03183 into cultured bladder epithelial cells (T24) was significantly reduced at HMGN2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…In the K. pneumoniae and BSA groups, F-actin expression and stress fibers were increased and the average fluorescence intensity of F-actin was significantly increased as compared with that in the PBS group, which indicated that following infection, polymerized F-actin was enhanced. Of note, in the HMGN2 group, F-actin expression and average fluorescence intensity of F-actin were decreased, which indicated that HMGN2 inhibited K. pneumoniae 03183 invasion of lung cells directly through reducing the polymerization of F-actin, which is consistent with previous studies by our group (24,25).…”
Section: A B Csupporting
confidence: 91%
See 3 more Smart Citations
“…In the K. pneumoniae and BSA groups, F-actin expression and stress fibers were increased and the average fluorescence intensity of F-actin was significantly increased as compared with that in the PBS group, which indicated that following infection, polymerized F-actin was enhanced. Of note, in the HMGN2 group, F-actin expression and average fluorescence intensity of F-actin were decreased, which indicated that HMGN2 inhibited K. pneumoniae 03183 invasion of lung cells directly through reducing the polymerization of F-actin, which is consistent with previous studies by our group (24,25).…”
Section: A B Csupporting
confidence: 91%
“…Is was able to inhibit the gene expression and replication of hepatic B virus in vitro (22) and also exhibited anti-cancer potency in HeLa cells (23). Further studies by our group demonstrated that pre-treatment of K. pneumoniae 03183 with 128 µg/ml HMGN2 significantly inhibited the internalization of K. pneumoniae 03183 into human bladder carcinoma T24 cells by decreasing K. pneumoniae-induced actin polymerization (24,25).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Human uroepithelial cells, T24 (ATCC HTB-4), were purchased from the Cell Bank of the Chinese Academic of Science (Shanghai, China) and cultured in RPMI 1640 medium (Hyclone Thermo Scientific, Beijing, China) with 10% fetal bovine serum (FuMeng Gene Co., Ltd., Shanghai, China), 100 U/mL penicillin, and 100 µg/mL streptomycin (Beijing Solarbio Science and Technology Co., Ltd., Beijing, China) at 37 °C in humidified air with 5% CO 2 . Adherence assay was performed according to a previous method [ 37 ]. Briefly, an appropriate number of T24 cells were seeded into a 24-well plate and allowed to grow overnight to 2 × 10 5 cells each well.…”
Section: Methodsmentioning
confidence: 99%